Strive to Succeed? The Role of Persistence in the Process of Educational Attainment - Alberto Palacios-Abad (American Behavioral Scientist, 2021)
This article examines the role of effort in the process of educational attainment. First, I analyze the impact of effort on future tertiary educational attainment. Then, I test two sociological theories that argue that effort transmits educational inequality across generations. According to the first theory, parental background shapes the effort that children exert in education-related activities. The second theory argues that the drivers of effort in this context are educational expectations. I use a variable for effort that is measured directly over the course of the Programme for International Student Assessment test. Using a longitudinal data set from Australia, I estimate different hierarchical and structural equations models. I find that the measure of effort is positively and significantly associated with the probability of having obtained a tertiary degree 10 years later. Furthermore, the results show partial support for the second theory but not for the first one.
doi:10.25384/SAGE.14248332.v1
Keywords: 300; persistence; educational attainment; parental background; expectations; educational inequality